Profil Gratitude Mahasiswa - Fajar Ilham; Nandang Rusmana; Nandang Budiman (Journal of Innovative Counseling : Theory, Practice, and Research, 2019)
This study aims to determine the condition of gratitude for new students in the geography education study program at Indonesia University of Education. This research is a quantitative research with descriptive method. The instrument used in this study is the scale of gratitude. The subjects in this study were 78 new students in the 2018/2019 geography education study program. Data analysis in this study used descriptive statistics with percentage techniques. The results showed that 14,1% of students had high gratitude, 47,4% of students had medium gratitude, and 38,5% of students had low gratitude. The results of this study were useful for lecturer